2023
DOI: 10.5114/aic.2023.124742
|View full text |Cite
|
Sign up to set email alerts
|

World Federation for Interventional Stroke Treatment (WIST) multispecialty training guidelines for endovascular stroke intervention

Abstract: Introduction: Today, endovascular treatment (EVT) is the therapy of choice for strokes due to acute large vessel occlusion, irrespective of prior thrombolysis. This necessitates fast, coordinated multi-specialty collaboration. Currently, in most countries, the number of physicians and centres with expertise in EVT is limited. Thus, only a small proportion of eligible patients receive this potentially life-saving therapy, often after significant delays. Hence, there is an unmet need to train a sufficient number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…WIST are using their guidelines and establishing clinical knowledge and procedural skills to raise the capability requirements of interventionalist to perform endovascular stroke intervention. 34 Likewise, collaborate with ANGELS Academy provide e-learning program for stroke care knowledge and skills is potential to enhance the competency of neurointerventionist. 35 Providing a proctoring session to the fellow via telemedicine can increase the rate of IVT in many hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…WIST are using their guidelines and establishing clinical knowledge and procedural skills to raise the capability requirements of interventionalist to perform endovascular stroke intervention. 34 Likewise, collaborate with ANGELS Academy provide e-learning program for stroke care knowledge and skills is potential to enhance the competency of neurointerventionist. 35 Providing a proctoring session to the fellow via telemedicine can increase the rate of IVT in many hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…The training requirements should be based on skills; medical specialty should be of no importance. Indeed, physicians of various specialities experienced in endovascular procedures have long demonstrated that they can gain additional knowledge and training to perform EST and be an extremely valuable part of this developing system [ 12 , 13 ]. The required time for diagnostic neuroradiology training is 12–24 months (on top of years of radiology training), and for interventional neuroradiology it is 12–30 months [ 14 23 ].…”
mentioning
confidence: 99%
“…Embolization of arteriovenous malformations or spinal angiograms are not part of EST. The WIST guidelines [ 12 , 13 ] present an important evolution, encompassing an individualised approach to operator training. An interventionalist experienced in carotid stenting has already acquired an essential part of the skillset required for EST.…”
mentioning
confidence: 99%
“…An agreement was reached with the General Medical Council and the UK Royal College of Radiologists that experienced clinicians who are not interventional neuroradiologists could -and should -undertake training to equip them with the skills to undertake thrombectomy alone, based on pre-existing knowledge and skills (such as advanced intra-arterial catheter skills). By mapping out a training and credentialing pathway for interventionalists from varying backgrounds, WIST guidelines [4,5] finally provide a truly collaborative, competency-based, global solution for increasing the number of endovascular stroke treatments for eligible patients with acute ischaemic stroke [6][7][8][9][10][11][12][13][14][15][16]. The WIST training and credentialing strategy has already been effective in different healthcare systems across the world and, more recently, in Scotland, where safe and effective training according to WIST guidelines has been established.…”
mentioning
confidence: 99%